Syarat-syarat dan Prosedur dalam al-Jarh wa al-Ta’dil - Kurniawan, Irwan; Mujoko, Bejo; Azzami, Abdulloh; Hairullah, Hairullah; Arifin, Tajul (Lembaga Yasin AlSys, 2024)
The purpose of this article is to explain the terms and procedures of jarh wa ta'dil. a researcher must have in-depth knowledge of the terms and procedures of jarh wa ta'dil, because the science of jarh and ta'dil includes a discussion of a critic's assessment of the good and bad or defects of the hadith narrator. It is important to know the terms and procedures in jarh and ta'dil because they relate to a hadith and its rawi which is one of the conditions for accepting a hadith.